Population-genomic insights into emergence, crop adaptation and dissemination of Pseudomonas syringae pathogens. Issue 10 (October 2016) - Monteil, Caroline L.; Yahara, Koji; Studholme, David J.; Mageiros, Leonardos; Méric, Guillaume; Swingle, Bryan; Morris, Cindy E.; Vinatzer, Boris A.; Sheppard, Samuel K.
Abstract : Many bacterial pathogens are well characterized but, in some cases, little is known about the populations from which they emerged. This limits understanding of the molecular mechanisms underlying disease. The crop pathogen Pseudomonas syringae sensu lato has been widely isolated from the environment, including wild plants and components of the water cycle, and causes disease in several economically important crops. Here, we compared genome sequences of 45 P. syringae crop pathogen outbreak strains with 69 closely related environmental isolates. Phylogenetic reconstruction revealed that crop pathogens emerged many times independently from environmental populations. Unexpectedly, differences in gene content between environmental populations and outbreak strains were minimal with most virulence genes present in both. However, a genome-wide association study identified a small number of genes, including the type III effector genes hopQ1 and hopD1, to be associated with crop pathogens, but not with environmental populations, suggesting that this small group of genes may play an important role in crop disease emergence. Intriguingly, genome-wide analysis of homologous recombination revealed that the locus Psyr 0346, predicted to encode a protein that confers antibiotic resistance, has been frequently exchanged among lineages and thus may contribute to pathogen fitness. Finally, we found that isolates from diseased crops and from components of the water cycle, collected during the same crop disease epidemic, form a single population. This provides the strongest evidence yet that precipitation and irrigation water are an overlooked inoculum source for disease epidemics caused by P. syringae .